2015
DOI: 10.1371/journal.pone.0125919
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Retinal Nerve Fiber Layer Changes in Preclinical Diabetic Retinopathy: A Meta-Analysis

Abstract: BackgroundDiabetic retinopathy is a microvascular neurodegenerative disorder in diabetic patients. Peripapillary retinal nerve fiber layer changes have been described in patients with preclinical diabetic retinopathy, but study results have been inconsistent.ObjectiveTo assess changes in peripapillary retinal nerve fiber layer thickness in diabetic patients with preclinical diabetic retinopathy.MethodsA literature search was conducted through PubMed, EMBASE, Web of Science and Cochrane Library. Case-control st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 42 publications
(41 reference statements)
7
45
2
2
Order By: Relevance
“…In addition, significant retinal ganglion cell complex thinning has been reported in patients at early stages of diabetes, predating their retinal vasculpathy . And there is a well‐documented evidence to indicate that even in the absence of vascular changes, RNFL thickness around the optic disc become significantly thinner in eyes with type 2 diabetes compared with those without diabetes, and that the most frequent location of RNFL loss in diabetes was the superior hemisphere . However, it was still uncertain whether neural or vascular defects occurs first in the early onset of DR. Our study showed that average RNFL thickness and sector RNFL thickness in NS, SN and IN quadrants in diabetes were significantly thinner than those of normal controls, which was consistent with previous researches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, significant retinal ganglion cell complex thinning has been reported in patients at early stages of diabetes, predating their retinal vasculpathy . And there is a well‐documented evidence to indicate that even in the absence of vascular changes, RNFL thickness around the optic disc become significantly thinner in eyes with type 2 diabetes compared with those without diabetes, and that the most frequent location of RNFL loss in diabetes was the superior hemisphere . However, it was still uncertain whether neural or vascular defects occurs first in the early onset of DR. Our study showed that average RNFL thickness and sector RNFL thickness in NS, SN and IN quadrants in diabetes were significantly thinner than those of normal controls, which was consistent with previous researches.…”
Section: Discussionmentioning
confidence: 99%
“…However, growing evidences suggest that retinal neurodegeneration is present before the development of clinically detectable microvascular damage. A decrease in retinal nerve fibre layer (RNFL) thickness has been reported in patients with DM without clinical DR. 5 Recent studies have showed positive correlation between peripapillary vessel density and RNFL thickness at 3.45-mm circle diameter around the optic nerve head (ONH). Since peripapillary RNFL thinning is significant in preclinical DR, it is of interest to investigate the blood flow of ONH in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…, ; Cabrera DeBuc & Somfai ; Vujosevic & Midena ) and in the peripapillary region (Chen et al. ). However, in our preoperative analysis, the association was only borderline significant, which could be due to study size.…”
Section: Discussionmentioning
confidence: 99%
“…При проведенні метааналізу секторальної товщини шару перипапілярних нервових волокон сітківки у хворих на ЦД без діабетичної ретинопатії виявили витончення у верхньому нижньому та назальному секторах, але у темпоральному зміни не були вірогідними [7]. Згідно з даними А. Araszkiewicz зі співавторами, при ЦД I типу загальне витончення шару нервових волокон сітківки спостерігалось за рахунок верхнього та носового сегментів [4].…”
Section: таблиця 2 показники товщини перипапілярних нервових волоконunclassified